Financial Crises Resolutions: Monetary & Non-monetary Approaches - Wong, Pamela Chew Gek (2009)
This paper examines the solutions to financial crises in the current financial systems. Since globalisation helps the financial markets grown, the world’s markets became interrelated. Therefore, a failure in financial system of one country could results in financial instability in other countries which then leads to global financial crises. Massive global financial crisis normally brings the world’s economies into recession. My aim is to bring an understanding of causes and consequences of financial crisis in hope that this will bring with it an informed discussion of how monetary policy should be reformed. Although monetary policy had been strengthened alongside with the development of financial systems, we must acknowledge that its roles alone are not possible in maintaining financial stability due to the limitations on the monetary policy. I find that all the participants in the economy are jointly responsible for playing their roles in working for the solutions mechanism that may help either to avoid financial failure, to deals with the problems when it happened or to restore the financial systems. This paper contains the monetary policy and non-monetary approaches that had been put in place by monetary regulators and some new approaches suggested by academics for better regulations in the future.